Design, Synthesis, Biological Evaluation, and In Silico Study of N-(Pyridin-2/3-yl)alkanamide Derivatives as Quorum Sensing Inhibitors Against Pseudomonas aeruginosa - Jaiswal U.; Bhopale A.J.; Srivastava N.; Yerramsetti N.; Kumar R.; Kumar L.; Yadav A.K. (My University, 2025)
The effectiveness of treating bacterial infections is seriously jeopardized by the emergence of bacterial resistance to chemical therapy. The development of biofilm in bacteria is one of the main causes of resistance to antimicrobial drugs. By developing new antibiofilm medications, quorum sensing (QS) inhibitor was developed as an alternate therapy. QS inhibition, which focuses on the QS signaling pathway, obstructs cell–cell communication. The aim of this work is to develop newer QS inhibitors against Pseudomonas aeruginosa. N-(Pyridin-2/3-yl)alkanamide derivatives were designed as QS inhibitors, and these designed molecules were synthesized. QS inhibitor activity was evaluated for the synthesized compounds (3a–l, 4a–h). The highest QS inhibitor activities for compounds 3k, 4a, and 4c were 11.66 ± 0.11, 14.66 ± 0.15, and 10.66 ± 0.05 mm, respectively. Subsequent molecular docking analyses exhibited moderate to good binding affinity values between −7.1 and −9.3 kcal/mol. Using the in silico method, the physicochemical characteristics of these prepared compounds were examined. Additionally, molecular dynamic simulation was employed to gain a deeper comprehension of stability of the protein and ligand complexes of compounds 3k, 4a, and 4c. The overall findings of the study indicated that N-(pyridin-2/3-yl)alkanamide derivatives might be significant for the development of newer QS inhibitors. © 2024 Wiley-VCH GmbH.